Praktik Meditasi pada Penghayat Kepercayaan Sapta Darma: Konsep Sujud untuk Mencapai Kesadaran Penuh - M. Naufal Firosa Ahda; Yusuf Ratu Agung (Reformed Center for Religion and Society, 2022)
This study aims to determine the concept of meditation in Sapta Darma and understand the effects and processes in achieving mindfulness (”satrio utomo”). This study used a qualitative research method with a phenomenological approach. Data collection techniques were conducted through in-depth interviews, observation, and documentation of the Sapta Darma believers who meditated (sujud). The results showed that sujud has several concepts that contain philosophical elements and affect the psychological side of the subjects. The psychological effect generally felt after practising meditation shows their full awareness. It can be achieved through several stages, including being able to control the